A Juridical Analysis of Healthcare Cost Transparency by Hospitals - I.Permadi; J.Kusnadi (International Medical Journal Corp. Ltd, 2025)
Introduction: Healthcare cost transparency has become a pivotal issue in modern medical jurisprudence, driven by the persistent asymmetric information between healthcare providers and patients. This study examines the legal obligations of hospitals to disclose medical costs openly and the mechanisms available to protect patient rights as vulnerable consumers. Methods: This study employs a normative juridical research method, analyzing primary legal materials such as health regulations and consumer protection laws, alongside secondary legal sources including academic journals and jurisprudence. Results: The analysis reveals that while explicit statutory mandates require hospitals to provide clear, upfront cost structures, implementation remains fragmented due to vague enforcement clauses and institutional resistance. Current regulatory frameworks fail to provide standardized disclosure formats, leading to hidden fees and unpredictable billing. Discussion: The discussion synthesizes existing literature on medical consumerism and legal liability. It highlights a critical research gap: the lack of punitive alignment between consumer protection statutes and healthcare administrative laws. The novelty of this research lies in its formulation of a unified juridical model that integrates contractual transparency into electronic medical administration. It underscores how pricing opacity violates the legal principle of informed consent, which should extend from medical procedures to fiscal liabilities. Conclusions: This study concludes that healthcare cost transparency is a mandatory legal right rather than a discretionary administrative policy. To bridge existing statutory loopholes, governments must institute rigid, standardized electronic price disclosure systems backed by strict administrative sanctions for non-compliance.